2018
DOI: 10.1002/lary.27314
|View full text |Cite
|
Sign up to set email alerts
|

Snoring and carotid artery disease: A new risk factor emerges

Abstract: 2b Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…Selfreported snoring was demonstrated to be related to subclinical atherosclerosis, 7 high-risk carotid plaque features, 50 or bilateral carotid artery stenosis. 51 However, some research…”
Section: Discussionmentioning
confidence: 99%
“…Selfreported snoring was demonstrated to be related to subclinical atherosclerosis, 7 high-risk carotid plaque features, 50 or bilateral carotid artery stenosis. 51 However, some research…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis, confirmed that CIMT was higher in OSA patients compared to healthy controls (SMD = 0.810 CI: 0.676-0.943; P < 0.001) with a fair correlation between AHI and CIMT (R = 0.389; 95% CI: 0.315-0.459; P < 0.001). Further studies published after these two metaanalyses deserve to be reported [55][56][57][58][59][60][61][62][63][64]. A total of 206 adults newly diagnosed with OSA (AHI of 15-75 events/h) and 53 controls with AHI < 10 were studied by Kim et al [55].…”
Section: Carotid Atherosclerosismentioning
confidence: 99%
“…Поширеність апное складає 5-7% в популяції старше 30 років. Поширеність простого хропіння у чоловіків середнього віку знаходиться в діапазоні 25-50% [1], тоді як значне порушення дихання уві сні зачіпає до 8% чоловіків і 3% жінок (данні недавнього проспективного дослідження населення "Спляче серце " (6441 осіб) [2].…”
Section: оглядиunclassified